How Does the National Big Data Comprehensive Pilot Zone Affect the Technical Complexity of Urban Exports? - Huang, Zhen (Transactions on Economics, Business and Management Research, 2023)
Taking "the establishment of the national big data comprehensive pilot zone" as a quasi-experiment, this study uses propensity score matching-difference in difference (PSM-DID) to investigate how the national big data comprehensive pilot zone improves the technical complexity of urban exports and its mechanism, which is based on the data of 280 prefecture cities from 2007 to 2019. The results show that the establishment of national big data comprehensive pilot zone can improve the technical complexity of urban exports. Specifically, it drives regional trade upgrading by increasing technology investment. In addition, its establishment has inhibited the technical output to some degree, and the trade openness negatively regulates the impact of the big data comprehensive pilot zone on the technical complexity of urban exports. Besides, this study not only lays a foundation for empirical research on the national big data policy to promote the high-quality development of regional trade, but also provides a new perspective for studying the transformation of digital economy.